Timely course of SARS-CoV-2 infections and vaccinations in patients with hemato-oncological diseases: analysis of a real-life cohort - Mair, M.J.; Mitterer, M.; Buratti, T.; Berchtold, L.; Fong, D.; Preusser, M. (ESMO open, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has particularly impacted patients with hemato-oncological malignancies, as they showed not only a higher propensity for severe courses but also weaker immune responses after vaccination. Still, data on the influence of pandemic waves and vaccinations on outcomes are rare. This study aimed to analyze the timely course of infections and vaccinations in a real-life cohort of patients with hemato-oncological diseases. In this cohort study, 1817 patients with hemato-oncological diseases from 1 February 2020 to 15 December 2022 at the ‘Franz Tappeiner’ Hospital in Merano/Meran, Italy, were followed for SARS-CoV-2 infections and vaccinations. Of 1817 patients with hemato-oncological malignancies, 735 (40.5%) were infected at least once with SARS-CoV-2, and 1614 (88.8%) received one or more doses of the approved vaccinations. Patients receiving antineoplastic treatment had a lower SARS-CoV-2 infection rate [35.1% versus 41.0%; odds ratio (OR) 0.78, 95% confidence interval (CI) 0.64-0.95], but higher risk of hospitalization (13.4% versus 6.9%; OR 2.11, 95% CI 1.25-3.69) compared with untreated patients. Overall, the case fatality rate (CFR) was 3.4%. Unvaccinated patients were more prone to severe coronavirus disease 2019 (COVID-19) courses requiring hospitalization (OR 2.34, 95% CI 1.25-4.36) and had a higher CFR (7.3% versus 1.6%; OR 4.98, 95% CI 2.16-12.98) than their vaccinated counterparts. In the Delta wave, patients with two vaccinations had a lower infection risk (OR 0.18, 95% CI 0.10-0.35) and tendentially lower hospitalization rates (OR 0.25, 95% CI 0.05-1.29) than unvaccinated patients. In the Omicron wave, 345/1198 (28.8%) patients with three or more vaccinations had breakthrough infections, resulting in a similar risk for infection (OR 0.88, 95% CI 0.60-1.30) but numerically lower risk for hospitalization (24/345, 7.0%) than unvaccinated individuals (4/40, 10.0%). Scheduled visits were postponed in 128/335 (38.2%) patients due to COVID-19, and deferrals correlated with pandemic wave (P = 0.002) and vaccination status (P < 0.001). SARS-CoV-2 infections and outcomes differ between distinct phases of the pandemic. Vaccination with variant-specific vaccines should be prioritized as general protective measures are increasingly lifted. •Incidence of SARS-CoV-2 infections varied over the pandemic in patients with cancer.•Outcomes of COVID-19 considerably differ according to pandemic phase and vaccination status.•Overall, case fatality and hospitalization rates were lower in vaccinated patients.•Breakthrough infections in recent waves underline the need for variant-specific vaccines.